(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
One of the elements of sustainable hydropower development is the release of the environmental flows (Eflows). This Eflows is meant to ensure that prior use(r)s of the river water are respected and that essential riverine ecosystem functions are maintained. This paper presents the results of an e-flows assessment, using the hydrological index method, of Hewa Khola A and Lower Hewa Khola Hydropower Projects, in Phidim, Nepal. These projects are being developed in the tributaries of Tamor River in Eastern part of Nepal. The e-flows assessment results are compared with the current releases made from the projects in operation. Current operations are prone to lead to severe degradation and social conflict. Based on an evaluation of the effects of a higher Eflows release on the power production, the paper concludes with recommendations for appropriate Eflow releases, and thus for socially and environmentally sustainable operations of the hydropower projects. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 23 Year: 2018